Savitumas kaip vertybėarchitektūroje - Andriušytė, Aistė (Journal of Architecture and Urbanism, 2007)
Originality as value in architecture Originality is one of the most important qualities of an architectural object. Its relation with contextuality is ambivalent: these categories are evaluated according to personal approach which is formed by experience. The field of the sense of the originality concept is broad: e g stylistic unaniminity of epoch processes is cultural originality that presents the feeling of identity. The factor of originality and identity recognition is important with respect to familiar for man space places and to cultural novelty. The aspiration of a creator for self-expressioness in positive relation is suited to the motive of recognition, that is orientation to universal values. If originality is considered as universal value, it should be acknowledged with respect to both a new work of art and medium. As every place of natural space is unique, it is quite probable that an object created with respect to the context will be distinguished by its originality. Article in Lithuanian. Santrauka. Savitumas – viena svarbiausių architektūros objekto kokybių. Jo santykis su kontekstualumu yra ambivalentiškas: šios kategorijos vertinamos pagal asmeninį požiūrį, kurį formuoja patirtys. Sąvokos savitumas prasmių laukas platus: pavyzdžiui, stilistinis epochos reiškinių vientisumas yra kultūrinis savitumas, teikiantis tapatumo jausmą. Savumo, atpažinimo veiksnys svarbus ir žmogui pažįstamų erdvės vietų, ir kultūrinių naujovių atžvilgiu; kūrėjo saviraiškos siekis esant teigiamam santykiui dera su pripažinimo, t. y. su orientacijos į visuotines vertybes motyvu. Visuotine vertybe laikant savitumą, jis turi būti pripažįstamas ir naujo kūrinio, ir terpės atžvilgiu. Kadangi kiekviena iš natūralių erdvės vietų yra nepakartojama, labai tikėtina, jog objektas, sukurtas, atsižvelgiant į kontekstą, pasižymės savitumu. Reikšminiai žodžiai: vertybė, savitumas, kontekstualumas. First published online: 21 May 2013